Pendampingan dalam Memanfaatkan Media Pembelajaran Offline dan Online pada Siswa di Desa Kedungwaru Tulungagung di Masa Pandemi - Rohmatus Syafi'ah; Alik Mustafidal Laili (LPPM Universitas Flores, 2022)
Online learning is internet-assisted learning without direct face-to-face. Online learning has several weaknesses, including limited internet quota, children who are not comfortable studying at home, time constraints for parents in accompanying children to study, and so on that causes children not to focus on learning. Parents play an important role, especially in terms of providing understanding to their children regarding the covid-19 outbreak, staying at home, and accompanying their children in learning. Like the people in Kedungwaru Village, many parents feel overwhelmed by accompanying their children to study at home. Obstacles faced include parents having to rack their brains to divide their time between working and accompanying their children to study, parents' lack of understanding of children's learning materials, and limited internet quota. Therefore, this Community Service (PkM) aims to help children in Kedungwaru village by assisting children in learning by using online and offline learning media. The method of implementing the activities includes the preparation stage (initial survey and problem identification), implementation stage (socialization and assistance in utilizing online and offline learning media for 8 elementary school students and 2 junior high school students in Kedungwaru Tulungagung village), program evaluation stage, and finally reporting. The results obtained in this activity, the community in Kedungwaru village, elementary and junior high school students were helped in understanding the material taught by the teacher online. The use of online and offline learning media increases enthusiasm for learning because by using the media, they can immediately practice practicum-based learning activities, such as the use of caliper, screw micrometer, and the process of blowing balloons using baking soda and vinegar. The follow-up plan for this activity is the continuation of PkM activities in the following year.